2013
DOI: 10.1530/erc-13-0233
|View full text |Cite
|
Sign up to set email alerts
|

Serum estrogen receptor bioactivity and breast cancer risk among postmenopausal women

Abstract: The estrogen levels of Asian women are different from those of Western women, and this could affect estrogen receptor (ER) bioactivity and breast cancer risk. We conducted a case-control study of 169 postmenopausal breast cancer cases and 426 matched controls nested within a population-based prospective cohort, The Singapore Chinese Health Study, to evaluate serum levels of estrogens and their receptor (ERα and ERβ)-mediated estrogenic activities in relation to breast cancer risk. Breast cancer cases had highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…It is unclear from our results if the lower E activity is due to lower levels of endogenous estrogens or lower levels of endocrine disruptors, and further studies will need to be conducted to clarify these results. Targeted studies looking at the association between endogenous estrogens and breast cancer risk have already shown a positive relationship (25,26), and a previous study of E activity in Asian women strongly suggested increased activity among women who developed breast cancer, beyond the effect of endogenous estrogen levels (19). Analyses did not include variables such as age at menarche, number of live births and breastfeeding, which are important breast cancer risk factors related to variation in estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is unclear from our results if the lower E activity is due to lower levels of endogenous estrogens or lower levels of endocrine disruptors, and further studies will need to be conducted to clarify these results. Targeted studies looking at the association between endogenous estrogens and breast cancer risk have already shown a positive relationship (25,26), and a previous study of E activity in Asian women strongly suggested increased activity among women who developed breast cancer, beyond the effect of endogenous estrogen levels (19). Analyses did not include variables such as age at menarche, number of live births and breastfeeding, which are important breast cancer risk factors related to variation in estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically Activated LUciferase gene eXpression, or CALUX, bioassays are highly sensitive and reliable high throughput screenings used to measure biologically relevant exposures in various media including sediment (13), house dust (14), drinking water (15,16) and human blood (19,20). CALUX assays are used to identify receptor-mediated signaling pathways of gene expression by specific compounds such as estrogens and androgens (44,45).…”
Section: Luciferase Assay Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Using mammalian cells transfected with ERE-luciferase reporter vector, conventional ER bioassays have been used to detect bioactiviy in human samples [69]. Especially for breast cancer studies in postmenopausal women, ER bioassays can predict an increased risk of postmenopausal breast cancer independently from hormone levels [1012]. In this study, we demonstrated directly that the detectable estrogenic activity in tested human serum samples correlated with the sample's ability to promote the proliferation of breast cancer cell line MCF-7aro.…”
Section: Introductionmentioning
confidence: 99%